PERANCANGAN KONTEN KLIP EDUKATIF SEBAGAI STRATEGI ADAPTASI POLA KONSUMSI DIGITAL GEN Z TERHADAP KANAL YOUTUBE BRIN - Muhammad Syafiq Rifaza; Rici Tri Harpin Pranata; Harries Marithasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Changes in Generation Z’s digital media consumption patterns have created a growing demand for information that is concise, accessible, and easy to understand. This trend presents a challenge for the National Research and Innovation Agency (BRIN), which primarily disseminates scientific information through long-form YouTube content such as webinars, talk shows, documentaries, and podcasts. This study aims to identify Generation Z’s digital content consumption patterns, design an educational clip format that aligns with their media preferences, and describe the content development process implemented on BRIN’s YouTube channel. The study employed a descriptive qualitative approach, with data collected through observation, active participation, and discussions conducted during an internship program at BRIN TV. The findings indicate that many long-form videos on BRIN’s YouTube channel contain valuable segments that can be repackaged into concise and engaging educational clips. These educational clips serve as a communication adaptation strategy by presenting scientific information in a format that better suits Generation Z’s media consumption habits while maintaining the integrity and substance of the original content.